Determining the Dynamics of Apartment Prices in a Construction Company Using the STATISTICA Software - Motskobili, Ia; Takidze, Irma; Surmanidze, Inga (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
The real estate market in Batumi has emerged as one of the most dynamic sectors, characterized by growing demand from both local and foreign buyers. This study aims to identify the key factors affecting apartment prices and to perform a statistical analysis using the STATISTICA software. The dataset covers 153 apartments described by parameters such as area (m²), price per square meter, total price, number of rooms, floor, comfort level, and geographical location. The analysis revealed notable variations in prices across districts and significant correlations between apartment characteristics and overall value. The results are relevant for economic analysis as well as for practical decision-making by buyers, investors, and developers.